An approach to quantitative assessment of hemodynamic differences between unruptured and ruptured ophthalmic artery aneurysms. Issue 13 (2nd October 2016) - Yu, Hongyu; Li, Haiyun; Liu, Jian; Yang, Xinjian
Abstract: Background and purpose : Hemodynamic parameters are important in the pathogenesis, evolution and rupture of intracranial aneurysm. Energy loss (EL) has been applied for the rupture risk prediction of artery aneurysms recently. We proposed a new EL and further investigate its effects on the rupture of aneurysms. Materials and methods : Sixty-four patient-specific ophthalmic aneurysm datasets were divided into ruptured and unruptured groups based on their clinical history. Based on patient-specific 3D-DSA data, realistic models were retrospectively reconstructed and then analyzed by using computational fluid dynamic method. Results : The flow field feature EL in ruptured cases was significantly higher than that in unruptured cases. The average wall shear stress (WSS) and the maximum WSS in ruptured cases were higher than those in unruptured cases. Modified pressure loss coefficient (PLCM ) in ruptured cases was slight higher than that in unruptured cases but the difference has no statistical significance. Multivariate logistic regression analysis demonstrated flow field feature EL ( p  < 0.05) and the maximum WSS ( p  < 0.05) were the only independently significant variables to predict rupture of ophthalmic aneurysm. There were no differences in PLCM, the maximum oscillatory shear index (OSI), the average OSI and AR between the two groups. Conclusion : Flow field feature EL may be a reliable factor to predict the rupture risk of aneurysms.